WELFARE FARMS IN POLAND AS AN EXAMPLE OF ENTREPRENEURIAL ACTIVITIES IN RURAL AREAS - Wojcieszak, Monika (Proceedings of the International Scientific Conference "Economic Sciences for Agribusiness and Rural Economy", 2018)
The purpose of the paper was to present the importance of welfare farms in Poland as a social element of mutual relations, connections and co-operation in local and regional development. The concept of welfare farms is characterised in the study and the main idea of their formation is presented. Examples of welfare farms in Poland as part of the first pilot project known as ‘Zielona opieka – gospodarstwa opiekuńcze w woj. kujawsko-pomorskim’ (Green care: welfare farms in the Kujawsko-Pomorskie voivodeship) have also been presented. It was also pointed out that social farming plays an increasingly important role in the contemporary development of rural areas. The paper was compiled using the desk research method and a classical analysis of documents was used. The choice of methods was determined by the availability of source materials, some of which were of primary or secondary nature (social farming literature, reports and public statistic documents). This paper also pointed to the fact that welfare farms are increasingly becoming a popular form of social service in rural areas. It also testifies to the entrepreneurship of farmers, because they offer not only accommodation and catering, but also care on their farms.